2018
DOI: 10.1159/000493507
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging: A New Tool for the Diagnosis of Bladder Pain Syndrome/Interstitial Cystitis

Abstract: Objectives: To determine whether diffusion-weighted magnetic resonance imaging (DWMRI), a noninvasive procedure, can contribute to the diagnosis of bladder pain syndrome/interstitial cystitis (BPS/IC). Methods: The pelvic DWMRI of patients with chronic pelvic pain syndrome was selected between January 2012 and June 2017. A radiologist analyzed the bladder wall signal; he was blinded to the patients’ clinical data. According to the 2008 European Society for the Study of Bladder Pain Syndrome/Interstitial Cystit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…Another study attempted to use diffusion-weighted MRI to diagnose BPS/IC. In this study of 106 patients, a high signal intensity of the bladder wall was related to the presence of BPS/IC (sensitivity 28%, specificity 88%), whilst no signal intensity was related to the absence of a BPS/IC (sensitivity 96%, specificity 29%) [56]. Using intravesical contrast, it was reported that MRI can also be used to assess bladder permeability, with greater contrast enhancement in BPS/IC compared with controls [57].…”
Section: Phenotype Based On Radiological Featuresmentioning
confidence: 68%
“…Another study attempted to use diffusion-weighted MRI to diagnose BPS/IC. In this study of 106 patients, a high signal intensity of the bladder wall was related to the presence of BPS/IC (sensitivity 28%, specificity 88%), whilst no signal intensity was related to the absence of a BPS/IC (sensitivity 96%, specificity 29%) [56]. Using intravesical contrast, it was reported that MRI can also be used to assess bladder permeability, with greater contrast enhancement in BPS/IC compared with controls [57].…”
Section: Phenotype Based On Radiological Featuresmentioning
confidence: 68%
“…These data are similar to the results reported by the Charlanes group. 4 The interpretation of the RD leads to the conclusion that among subjects who present a positive DW-MRI signal the incidence of cases of interstitial cystitis is higher, and there is a statistically significant difference compared to patients who do not have a high DW-MRI signal. Having a positive signal is therefore suggestive of interstitial cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…19 Fulguration using electrocautery via a Bugbee electrode was described by with HLD. 30,31 Cystoscopy under anesthesia is essential in the diagnostic algo- Primarily, the lack of a control group is a significant limitation, especially in BPS/IC in which the placebo effect is known to be as high as 50% in placebo-controlled trials. 32,33 Additionally, a limitation is the fact that all patients also concurrently underwent hydrodistension at the time of laser ablation which may have affected the symptomatic outcomes reported.…”
Section: Discussionmentioning
confidence: 99%